Fugitive species in a harlequin environment: Ants (Hymenoptera : Formicidae) and banana baits in the Amazon - Fowler, H. G.; Moutinho, PRS (Kansas Entomological Soc, 1997)
A total of 9 ant species were sampled from four sites covering 2000 km in the Amazon Basin using banana fruit baits: two sites on the Jurua River, one site on the Xingu River and in a dry forest of eastern Amazon, Paragominas. Camponotus abdominalis was present in all sites, and Camponotus sericeiventris, Camponotus sp. and Crematogaster sp. were present in two sites. All other species were present in only one site. Paragominas had the highest species richness because of a higher number of site restricted species. However, Jaccard faunas similarities among sites were not significantly related with distance between sites. Mosaic diversity showed a relatively simple taxonomic composition. The strong differences of the fauna sampled at banana fruit baits from other reported Neotropical ant faunas suggests that the fauna represents widespread fugitive species in an apparently complex environment.